Urbanisation in Bengal : ideas, institutions and policies - Chakravarty, Pallavi (London : Routledge, 2024)
"This volume presents a comprehensive study of the urbanization of Bengal from ancient to postcolonial times. It analyses the notion of urban space, examines the institutions which constitute the 'urban', and explores the crises brought about by the Partition. The book highlights the key features of urbanization in colonial Bengal--the print culture, institutions of Western education and Western medicine, and the census as a 'modern form of knowledge'. It also looks at the refugee movement and discusses the contribution of Partition refugees in urbanizing Bengal. Rich in archival sources, this book will be indispensable for scholars and researchers of urban history, urban studies, Indian history, colonial history, postcolonial studies, partition studies, and South Asian history, particularly those interested in Bengal"--
Early historic urbanization in Bengal : Bangarh, a case study / Chirantani Das -- Cities of the mind : representing the urban in colonial Bengal / Kaustubh Mani Sengupta -- Popular print culture in the late 19th and early 20th century Calcutta / Shrobona Banerjee -- Breaking barriers : women's movement and writings from late colonial Bengal / Nilanjana Paul -- Struggle for space : Bengali women and urbanization of colonial Calcutta / Ata Mallick -- The politics of census : Bengal and the 1941 Population Enumeration / Subhasri Ghosh -- From refugees to citizens popular protests In West Bengal 1947-60 / Sutapa Dasgupta -- Carrying on the 'rural home' in the midst of the 'urban jungle' : refugee colonies in the post-partitioned Calcutta / Anindita Ghoshal and Urvi Mukhopadhyay -- 'Refugee-woman' in post-partition Bengal : a critical re-assessment of their roles and image / Pallavi Chakravarty -- Industrialization, migration and (un)making of a city : Durgapur experience / Abhinandan Das.
Keywords: Urbanization -- India -- Bengal; Bengal (India) -- Social conditions; HISTORY / General; SOCIAL SCIENCE / Sociology / Urban; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development